Beyond Commercial Ijarah: The Legal Construction of a Pesantren-Based Lease Model in Indonesian Islamic Economic Law - Mikail Mikail; Sunardi Sunardi; Abdul Rokhim (Borneo International Journal of Islamic Studies, 2026)
This study aims to examine the legal construction of the ijarah contract implemented in the leasing practices of Basmalah Stores owned by Sidogiri Islamic Boarding School and to compare it with Islamic banking ijarah and Ijarah Muntahiya Bit Tamlik (IMBT) within the framework of Indonesian positive law. Previous studies have predominantly focused on ijarah in Islamic financial institutions, leaving community-based implementations within pesantren economic institutions largely unexplored. This study contributes to the development of a community-based Islamic economic model by integrating legal validity, socio-religious values, and economic empowerment into the conceptual framework of ijarah. This research employed a normative legal approach with a comparative design. Data were obtained from twelve legal and academic sources, including statutory regulations, the Compilation of Islamic Economic Law, DSN-MUI fatwas, and contemporary scholarly literature. Data were analyzed qualitatively through descriptive, comparative, and prescriptive approaches. The findings reveal that Basmalah Stores apply pure ijarah (ijarah al-manÄfi”˜), characterized by the transfer of usufruct rights without ownership transfer. The contract fulfills the legal requirements stipulated in the Compilation of Islamic Economic Law, DSN-MUI Fatwa No. 09/2000, and the Indonesian Civil Code, with no indication of gharar, coercion, or unlawful purposes. Comparative analysis across eight aspects demonstrates that, unlike Islamic banking ijarah and IMBT, Basmalah’s ijarah emphasizes social welfare, community empowerment, and the sustainability of pesantren-based businesses. These findings position Basmalah’s leasing practice as a distinctive model of community-based Islamic economy that integrates legal compliance, social responsibility, and economic resilience.